Construction and Practice of Intelligent Data Analysis Center Based on Distributed Power Plant - Yuejin Su; Yingjie Han (Dianxin kexue)
Power generation groups fall dilemma in the high parameter units with less experts. It is necessary for a good optimization planning that the field experts analyze the equipments historical data and extract useful information. For the intelligent data analysis center architecture of distributed power station group, the underlying data flow control system's overall structure was described and the implementation process of intelligent data was analyzed in detail. The results show that it approaches the intelligent diagnostics, device status trend assessment and economic performance evaluation by the light of the information technology in big data era.